Simple Modified Transvesical Prostatectomy with Minimum Incision and Endoscopic Vascular Control: A Case Report - Oliveira Almeida, Antônio Carlos; Mitre, Anuar Ibrahim; Silva, Elcio Dias (Archives of Case Reports, 2025)
This work aims to report a case where a minimum incision and with vascular control endoscopically assisted transvesical prostatectomy was carried out to control hemostasis after prostate digital enucleation.